PENGARUH PROMOSI DAN KEMUDAHAN PENGGUNAAN TERHADAP LOYALITAS PELANGGAN PADA LAYANAN SHOPEEFOOD DI JAKARTA - Ranti Putri Pratiwi; Angga Putri Ekanova; Olivia Puspita Nagari (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to determine the effect of promotion and ease of use partially andsimultaneously on customer loyalty at shopeefood service in Jakarta. The analytical method in thisstudy uses quantitative primary data, the stages carried out are: data quality test, classical assumptiontest, multiple linear regression analysis, t test (partial), f test (simultaneous), coefficient of determination(R2) using tools spss testing. The data used in this study were obtained by distributing questionnaires to100 respondents. The results of this study indicate that the promotion variable can partially andsignificantly affect customer loyalty at Shopeefood services in Jakarta. The ease of use variable partiallyand significantly can effect customer loyalty at ShopeeFood services in Jakarta. There is a simultaneousand significant influence between the variables of promotion and ease of use on customer loyalty atShopeeFood service in Jakarta.